PENGARUH BUDAYA KERJA ORGANISASI, KOMPETENSI, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (TINJAUAN PUSTAKA SDM) - Ubaidillah, Ibnu; Faeni, Dewi Puspaningtyas (SINERGI : Jurnal Riset Ilmiah, 2025)
The purpose of this study is to develop hypotheses about the influence between variables that will be used in further research within the scope of human resource management. The writing method used in this study is library research, drawing on previous research. Online resources such as Google Scholar, Publish or Perish, and other academic online resources were used to obtain previous research. The results of this study are: 1) The Influence of Organizational Work Culture on Employee Performance, 2) The Influence of Competence on Employee Performance, and 3) Work Motivation on Employee Performance.